IN VITRO ANTIPLASMODIAL ACTIVITY OF COUMARIN 8-HYDROXYISOCAPNOLACTONE-2',3'-DIOL ISOLATED FROM Micromelum minutum (G. Forst.) Wight & Arn - Ratna Asmah Susidarti (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2014)
Malaria remains a health problem in tropical and subtropical countries. The spread of antimalarial resistant parasites has prompted the research to find more effective new antimalarials. One strategy to discover new antimalarial drugs is through the exploration of medicinal plants traditionally used to treat malaria. Micromelum minutum is one of medicinal plants has been used to treat malaria and other infectious diseases in Malaysia. The coumarin 8-hydroxyisocapnolactone-2¢,3¢-diol has been isolated from this plant and showed to have strong cytotoxic activities. This study aimed to evaluate the in vitro antiplasmodial activity of 8-hydroxyisocapnolactone-2¢,3¢-diol against chloroquine-resistant (FCR-3) and chloroquine-sensitive (D-10) Plasmodium falciparum. Culture of P. falciparum was continuously grown using a candle jar. Antiplasmodial assay was conducted by microradioactive method. The antiplasmodial activity was expressed by the IC50 indicating the concentration of the compound yielding 50% inhibition of the parasit growth. The results showed that 8-hydroxyisocapnolactone-2¢,3¢-diol has in vitro antiplasmodial activity against FCR-3 and D-10 with the IC50 values of 6.39 µg/mL (16.99 μM) and 24.23 μg/mL (64.45 μM), respectively.Key words: 8-hydroxyisocapnolactone-2’,3’-diol, M. minutum, anti-plasmodial activity, P. falciparum, FCR-3, D-10